Strategic Issue Management in Opposing Land Grab, Environmental, and Humanitarian Violation of Super Premium Tourism Development - Wijaya, Janies (Journal La Sociale, 2025)
The development of Indonesia’s strategic national-scale project in turning Komodo National Park as a Super Premium Tourism Destination resulted agrarian issues, including local communities’ land grab, environmental, and humanitarian issues. The government has violated so many aspects to accelerate the project delivery and has made the people of East Nusa Tenggara, specific to the people of Komodo, Labuan Bajo, and western Flores Island as the victim from the negative impacts of the development. Local communities have expressed their voice to the government, demanding fairness and basic rights to be fulfilled. Instead, they have to endured repressive actions and intimidation from the authorities, while the requested requirements met the dead end. The government has been ignoring the demand and never included the impacted local communities and activists in the discussion. Responding to this controversy, UNESCO also raised their concerns and requested the government to submit an Environmental Assessment report, and demand to stop the development until the requirements are met. This article proposes strategic action to National Committee on Agrarian Reform and other related entities in advocating this group and the ecosystem in the region in fighting to get their demand fulfilled by the government through an agrarian reform. As challenging as it is, direct lobby to the government has to be done. To strengthen the pressure, this communication strategy plan to acquire the power of the Indonesian Netizen by creating public sphere, through public opinion war and media scrutiny, to make the issue going viral and push the government for immediate agrarian reform.